Oral hygiene habits of dentistry students that perform clinical practices in Technological Equinoccial University - Carrera, Alex (2017)
Objectives: Identify oral habits of dentistry students that performed clinical practice. Material and method: This study is an observational, descriptive and quasi-experimental, considering 35 students as a sample, with some variables like; healthy oral hygiene habit index, related with, sex, level of education and socioeconomic status. Results: 63% of participants were woman, the high percentage of participants (89%) were clasificated in middle socioecoomic status, while 71% of students had healthy oral hygiene habit index (p=0,03). Conclusions: Students of Universidad Tecnológica Equinoccial that performed clinical practice had good hygiene habits, college life and lifestyles with irregular schedules and extra activities, distorts habits established until that moment.